Development of Facilities and Infrastructure in the Management of Islamic Boarding School Jauharul Falah al-Islami, Kumpeh Ulu, Muaro Jambi Regency - Anggraini, Dian; Rusmini, Rusmini; Yusria, Yusria (LPPPIPublishing, 2025)
The focus of this research is to basically describe and discover the concept of Islamic boarding school management based on the development of facilities and infrastructure in the management of thejauharul Falah Al-Islami Islamic boarding school in Sungai Terap Kumpeh Ulu Muaro Jambi. A significant problem is that no guidelines have been created to regulate the implementation of programs related to Islamic boarding school facilities and infrastructure. The descriptive-analytical approach in this research took three phases, namely: explanation of theory, description of facts in the field, analysis of the suitability between theory and practice. Data collection techniques use observation, interviews and documentation. Data analysis uses the Miles and Huberman model and data validity techniques use data triangulation. The research found that the development of facilities and infrastructure in the management of the Jauharul Falah Al-Islami Islamic Boarding School in Sungai Terap Kumpeh Ulu Muaro Jambi, starting from planning as the initial foundation and as an important point in determining the success or failure of a program, organization, implementation and supervision as a support for planning has not optimally followed modern management principles. This can be seen from the fact that there are no planning documents that are factually easy to access. The results of this research are the impact of the development of facilities and infrastructure on the quality of Islamic boarding school management, improvements and additions to facilities increase learning comfort, learning effectiveness, administrative efficiency, as well as the positive image of Islamic boarding schools in the eyes of the community, which has an impact on increasing the number of new student registrants.